If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5(x + -3)(2x + -6) = 0 Reorder the terms: -5(-3 + x)(2x + -6) = 0 Reorder the terms: -5(-3 + x)(-6 + 2x) = 0 Multiply (-3 + x) * (-6 + 2x) -5(-3(-6 + 2x) + x(-6 + 2x)) = 0 -5((-6 * -3 + 2x * -3) + x(-6 + 2x)) = 0 -5((18 + -6x) + x(-6 + 2x)) = 0 -5(18 + -6x + (-6 * x + 2x * x)) = 0 -5(18 + -6x + (-6x + 2x2)) = 0 Combine like terms: -6x + -6x = -12x -5(18 + -12x + 2x2) = 0 (18 * -5 + -12x * -5 + 2x2 * -5) = 0 (-90 + 60x + -10x2) = 0 Solving -90 + 60x + -10x2 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), '10'. 10(-9 + 6x + -1x2) = 0 Factor a trinomial. 10((-3 + x)(3 + -1x)) = 0 Ignore the factor 10.Subproblem 1
Set the factor '(-3 + x)' equal to zero and attempt to solve: Simplifying -3 + x = 0 Solving -3 + x = 0 Move all terms containing x to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + x = 0 + 3 Combine like terms: -3 + 3 = 0 0 + x = 0 + 3 x = 0 + 3 Combine like terms: 0 + 3 = 3 x = 3 Simplifying x = 3Subproblem 2
Set the factor '(3 + -1x)' equal to zero and attempt to solve: Simplifying 3 + -1x = 0 Solving 3 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -1x = 0 + -3 Combine like terms: 3 + -3 = 0 0 + -1x = 0 + -3 -1x = 0 + -3 Combine like terms: 0 + -3 = -3 -1x = -3 Divide each side by '-1'. x = 3 Simplifying x = 3Solution
x = {3, 3}
| 5x+2=8x-16 | | 9y+x=90 | | 3x-2-x=-6 | | 3x+ax=9 | | -6p-18=-54 | | 7x-4x+2=x+3 | | 3x+ax=8 | | 0.4x-.2=1 | | a-2/7=5 | | -5x-25=5x-8x+17 | | 0.83k=0.16 | | 0.6(x-2)-0.3x=0.4-3+5-0.5x | | Y-3/8=21/4 | | 19p=3971 | | X^2-13x=x-49 | | 4.5=n/0.6 | | 3x-1y=28 | | 12t-8t-2t= | | 10u-4+9u-2= | | 24=x-(-6) | | 6/7=3z | | ((x)-2)=1 | | -18/(2x-4.45) | | 3x+122=11x+6 | | 3(2b+4)=6 | | 3(1)=2x-5 | | ((x)-2)=2 | | 9(x+1)=2(3x+8) | | 5/9(28-32) | | -5.5+8m=10.1 | | a-4b-2/a2b2 | | 5*x=95 |